A two-step optimization model for quantifying the flexibility potential of power-to-heat systems in dwellings. (15th October 2018) - Oluleye, Gbemi; Allison, John; Hawker, Graeme; Kelly, Nick; Hawkes, Adam D.
Highlights: Flexibility quantification considers dimensions of time, energy and cost. Heat pumps integrated in dwellings to absorb surplus renewable electricity. Integrating thermal storage encourages surplus electricity absorption in summer. Prosumers analyzed heterogeneously. Number of active prosumers depend on the value placed on flexibility. Abstract: Coupling the electricity and heat sectors is receiving interest as a potential source of flexibility to help absorb surplus renewable electricity. The flexibility afforded by power-to-heat systems in dwellings has yet to be quantified in terms of time, energy and costs, and especially in cases where homeowners are heterogeneous prosumers. Flexibility quantification whilst accounting for prosumer heterogeneity is non-trivial. Therefore in this work a novel two-step optimization framework is proposed to quantify the potential of prosumers to absorb surplus renewable electricity through the integration of air source heat pumps and thermal energy storage. The first step is formulated as a multi-period mixed integer linear programming problem to determine the optimal energy system, and the quantity of surplus electricity absorbed. The second step is formulated as a linear programming problem to determine the price a prosumer will accept for absorbing surplus electricity, and thus the number of active prosumers in the market. A case study of 445 prosumers is presented to illustrate the approach. Results show that the number of active prosumers is affected by the quantity of absorbed electricity, frequency of requests, the price offered by aggregators and how prosumers determine the acceptable value of flexibility provided. This study is a step towards reducing the need for renewable curtailment and increasing pricing transparency in relation to demand-side response.